Flow physics of air pollutants dispersion: A case study in an urban street canyon in Baghbazar, Kathmandu - Biraj Khadka,; Binayak Lohani,; Arun Bikram Thapa,; Bibek Parajuli,; Neeraj Adhikari, (Advances in Engineering and Technology: An International Journal, 2023)
The alarming increase of hazardous pollutants in South Asian cities such as Kathmandu, Delhi, Mumbai, Dhaka, etc. risks the life of every individual there. A major source in the production of such harmful pollutants is vehicles and industries. A Computational Fluid Dynamics (CFD) approach is proposed to model the pollutants emitted by vehicles using different Reynolds Averaged Navier Stokes (RANS) turbulence models in the street canyon setup. The primary aim of the study is to understand the effect of turbulence on the transport of gaseous pollutants in the street canyon. RNG k − ϵ model performed best among other turbulence models with mean FB -0.105, NMSE 0.045, FAC2 0.915 and R 0.93 which is validated with the experimental data. Higher wind speeds allowed the concentration to disperse more effectively in Baghbazar’s street canyon, resulting in lower concentrations of pollutants.